Recovering the Palestinian History of Dispossession through Graphics in Leila Abdelrazaq’s Baddawi - Priyadarshini, Arya; Sigroha, Suman (Eikón / Imago, 2020)
Documentation is a significant mechanism to prove one’s identity. Palestinians, being robbed of this privilege to document their history, have taken upon other creative means to prove their existence. Being instruments of resistance, graphics and comics have a historical prominence in the Palestinian community. Building on this rich history of resistance through art, the paper contends that the modern graphic novel is used as a tool by the author to reclaim the Palestinian identity by drawing their rootedness in the region, thus resisting their effacement from public memory.